2017
DOI: 10.14687/jhs.v14i1.4416
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the population density on quality of life

Abstract: The aim of this study was to compare life quality of people living in İstanbul, Ankara and İzmir having higher population density to those living in cities having lower population density. 2060 people from İstanbul, Ankara and İzmir, 5892 people from other cities, totally 7952 people, were participated in the study. Turkish version of WHOQOL-BREF scale consisting 27 items, developed by World Health Organization with the participation of 15 collaboration centers was used to determine life quality of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The impact of the built and natural environment on both physical and mental health has been noticed in many studies [13,58]. QoL in cities may be positively affected by higher population density in terms of social coherence [59]. However, overall life satisfaction tends to be higher in less densely populated areas [60], as long as non-densely populated areas combined with open spaces provide better neighborhood QoL [61].…”
Section: Criteria and Variablesmentioning
confidence: 99%
“…The impact of the built and natural environment on both physical and mental health has been noticed in many studies [13,58]. QoL in cities may be positively affected by higher population density in terms of social coherence [59]. However, overall life satisfaction tends to be higher in less densely populated areas [60], as long as non-densely populated areas combined with open spaces provide better neighborhood QoL [61].…”
Section: Criteria and Variablesmentioning
confidence: 99%
“…Many factors contribute to the quality of life. Among these, being "good" of life, one's happiness and doing things without being dependent on others and enjoying life can be listed (Başkan et al, 2017). Quality of life is defined as bed a satisfactory social situation in which the individual perceives bodily capacity limits (Orley and Kuyken, 1993;Bowling 1993).…”
Section: Turkish Studies -Social Sciencesmentioning
confidence: 99%
“…On the other variable was choose, population has more mixed type of research outcomes. Cramer et al [5] and Başkan et al [6] were the results about how does population density effect people's life. Cramer et al [5] demonstrated that having a high population density will lead to a high chance have mental illness, which can reduce the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Cramer et al [5] demonstrated that having a high population density will lead to a high chance have mental illness, which can reduce the quality of life. Whereas Başkan et al [6] indicated that people who live in an area with high population density were highly scored in four aspects: physiological, psychosocial, society and environment. There was a confliction of results between the two researches.…”
Section: Introductionmentioning
confidence: 99%